Schwannoma and Neurofibroma, Originating from the Ulnar Nerve in Neurofibromatosis: A Case Report and Review of the Literature - Ali Tabrizi; Ahmadreza Afshar; Iraj Mohebbi; Masoumeh Pourjabali; Hassan Taleb (The Surgery Journal, 2020)
Schwannomas and neurofibromas are rare benign tumors originating from the peripheral nerve sheath. Tumors in neurofibromatosis are mostly neurofibromas and often appear in the soft tissue of peripheral nerves. In this report, a patient presented with two large adjacent soft tissue tumors in the right wrist and distal forearm which originated from a common nerve. A schwannoma had formed beside a neurofibroma from the ulnar nerve and induced numbness and paresthesia in the little and ring fingers. Although the patient had café au lait spots on the skin, neurofibromatosis was not suspected due to lack of symptoms. The patient was referred to the current research clinic suffering from two soft tissue masses in the wrist and ulnar nerve dysfunction. In neurofibromatosis patients, two tumors of a different nature originating from a common nerve close together have rarely been described in the literature. The patient was treated by en bloc excision of the mass while protecting the nerve fascicles. The follow-up results indicated no neurological symptoms and complete restoration of ulnar nerve function.